2020
DOI: 10.1186/s12864-020-06912-4
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome-based selection and validation of optimal house-keeping genes for skin research in goats (Capra hircus)

Abstract: Background: In quantitative real-time polymerase chain reaction (qRT-PCR) experiments, accurate and reliable target gene expression results are dependent on optimal amplification of housekeeping genes (HKGs). RNA-seq technology offers a novel approach to detect new HKGs with improved stability. Goat (Capra hircus) is an economically important livestock species and plays an indispensable role in the world animal fiber and meat industry. Unfortunately, uniform and reliable HKGs for skin research have not been id… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 48 publications
0
26
0
Order By: Relevance
“…A total of eight candidate novel RGs were selected from the transcriptome data of A. acidoterrestris using the criteria including high expression levels (RPKM ≥ 10), and a low variability with CV ≤ 20%, MFC < 2.5, and DPM < 0.2 (Figure 2). Multiple studies have shown that transcriptomic data is a reliable source for exploring suitable RGs under specific experimental conditions, and similar criteria have been used for RGs screening in other species (Gao et al, 2018;Zhang et al, 2020;Xing et al, 2021). For A. acidoterrestris, all current studies on the functional gene expression used 16s rRNA as RG to normalize RT-qPCR data, but the stability of 16s rRNA has not been evaluated under specific conditions (Jiao et al, 2015;Feng et al, 2019;Zhao et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of eight candidate novel RGs were selected from the transcriptome data of A. acidoterrestris using the criteria including high expression levels (RPKM ≥ 10), and a low variability with CV ≤ 20%, MFC < 2.5, and DPM < 0.2 (Figure 2). Multiple studies have shown that transcriptomic data is a reliable source for exploring suitable RGs under specific experimental conditions, and similar criteria have been used for RGs screening in other species (Gao et al, 2018;Zhang et al, 2020;Xing et al, 2021). For A. acidoterrestris, all current studies on the functional gene expression used 16s rRNA as RG to normalize RT-qPCR data, but the stability of 16s rRNA has not been evaluated under specific conditions (Jiao et al, 2015;Feng et al, 2019;Zhao et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…As reported in the MIQE guidelines, normalization based on a single RG is not acceptable, and the optimal number of RGs must be experimentally determined (Bustin et al, 2009). Moreover, many studies indicated that the normalization with multiple RGs was necessary for the accurate assessment of gene expression under specific conditions (Noti et al, 2015;Zhang et al, 2020). The geNorm algorithm is usually used to determine the optimal number of RGs based on the pairwise variation (V n/n+1 ) (Vandesompele et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations